Games to motivate teaching athletics at early ages from Physical Education class - César Peraza Zamora; Carlos Alberto Morales Romero; María Lourdes Rodríguez Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
The present research, has its starting point in the existent problem for the development of Athletics in early ages, difficulty that coexists with the spreading and practice of this sport in the lessons of Physical Education in schools. For this research there has been taken a sample of students of 5th and 6th grades, between the 10 and 12 years old, from two primary schools, centering their attention to the Process of teaching-learning of athletics like object of the research. This work has been focused as objective to implement a group of alternative games to motivate the teaching of athletics from the earliest ages, through the lessons of Physical Education, contributing to the formation of the basic skills so that the student can go assimilating the different techniques in a leisure time. Different research methods were used; so much of the theoretical level, as of the empiric one, such as: analysis-synthesis, inductive-deductive, systemic-structural, analysis of documents, observation and the interview. Their application allows the professors to have a useful tool that can be used for its preparation, as well as the possibilities of generalization of the same one in other sports to motivate the lessons.